The DAO Liquid Crystal Spectropolarimeter dimaPol. Issue Volume 10:Issue S305(2014) (24th July 2015) - Monin, Dmitry; Bohlender, David; Hardy, Tim; Saddlemyer, Les
Abstract: The spectropolarimeter dimaPol measures circular polarization in spectral lines of stellar objects. The instrument is used to simultaneously detect polarization signals in the hydrogen Hβ line as well as nearby metallic lines. A fast switching ferro-electric liquid crystal waveplate synchronized with charge shuffling on the CCD is employed to greatly reduce instrumental systematics. dimaPol has been in use on the DAO 1.8-m Plaskett telescope since 2007. In this presentation we show the capabilities of the instrument as well as some of the main results obtained with it to date.